Fiber laser tuning by means of nonthermal plasma as a temperature regulator - Tung, Hao Jiun; Raja Ibrahim, Raja Kamarulzaman; Azmi, Asrul Izam; Husein, Nor Ain; Vargas-Rodriguez, Everardo; Alresheedi, Mohammed Thamer; Ng, Eng Khoon; Mahdi, Mohd Adzir (John Wiley and Sons, 2024)
This work presents a technique to obtain wavelength tuning for a fiber laser with a nonthermal plasma-based temperature regulator system and a fiber Bragg grating (FBG). The plasma effect was generated in a dielectric barrier discharge (DBD) reactor filled with helium as the carrier gas for plasma generation. The temperature characterization of the DBD reactor had shown that the nonthermal heating mechanism of plasma could manipulate gas temperature from 25°C to around 145°C in ~10 min. By exploiting the rapid temperature change of plasma, the reflected wavelength of the FBG can be tuned accordingly. At a discharge voltage of 3 kV, the fiber laser was tuned within a range of 2 nm with 11.9 pm/°C tuning resolution. The fiber laser exhibits a thermally stable emission with very low shifting at a constant temperature value. © 2024 Wiley Periodicals LLC.